Maxillofacial fracture due to traffic accidents in motorcycle riders with helmets - Kurniawan, Erza; Kasim, Alwin; Hambali, Herman (Universitas Padjadjaran, 2015)
Introduction: Many of maxillofacial fractures in traffic accidents, primarily occurred to motorcyclists. The fractures are strongly influenced by the use of helmets, either half-face or full-face helmets. The objective of this research was to obtain information about the fractures occurred to motorcyclist with helmets. Methods: The research was designed as a descriptive study and conducted in Oral and Maxillofacial Surgery Department of Hasan Sadikin Hospital. Results: From January 2009 through November 2011, recorded as many as 116 out of 759 fracture cases (15.28%). Based on its occurrence, male motorcyclist (80.17%) was found more often than female (19.83%). The study also recorded that based on the type of helmets, the accident occurred of those using half-face type (86.33%) and 13.67% to those using full-face type. Conclusion: Maxillofacial fractures in motorcycle accidents are recorded as many as 116 fracture cases. The most common type of maxillofacial fracture is a dentoalveolar fracture. Maxillofacial fracture more occurred in male.